Implementing Community-Informed Strategies to Improve Food and Nutrition Security of Families with Young Children - Amy R. Mobley; Alyssa Watkins; Nelta V. Timothee; Karla Shelnutt; Heather A. Eicher-Miller; Jennifer A. Weber; JeeWon Cheong; Jennifer Farrell; Lydia G. Shackelford (Journal of Nutrition Education and Behavior, 2026)

Beyond macrophages: FIPV tropism includes T and B lymphocytes - Aadhavan Balakumar; Patrawin Wanakumjorn; Kazuto Kimura; Ehren McLarty; Katherine Farrell; Terza Brostoff; Jully Pires; Tamar Cohen-Davidyan; Jennifer M. Cassano; Brian Murphy; Krystle Reagan; Amir Kol (Veterinary Microbiology, 2026)

Iterative Development of an Interactive Website to Support Shared Decision-Making in Metastatic Breast Cancer - Claire C. Conley; Sophia Cumbo; Jacqueline Chavez Ochoa; Afton Boles; Jennifer D. Rodriguez; Nicole Schwab; David Farrell; Suzan Abduljawad; Claudine Isaacs; Suzanne C. O’Neill (Journal of Cancer Education, 2024)

Impacts of drought and native grass competition on buffelgrass (Pennisetum ciliare) - Hannah L. Farrell; Jennifer Funk; Darin Law; Elise S. Gornish (Biological Invasions, 2022)

Disturbance is complicated: Headward‐eroding saltmarsh creeks produce multiple responses and recovery trajectories - Fengrun Wu; Steven C. Pennings; Collin Ortals; Jennifer Ruiz; W. Reilly Farrell; Samuel M. McNichol; Christine Angelini; Amanda C. Spivak; Merryl Alber; Chunfu Tong (Limnology and Oceanography, 2022)
Disturbances are one of the most important processes affecting natural systems, but there is a gap between simple conceptual models of disturbance and complex empirical studies. We studied the perturbation caused by headward‐eroding creeks in southeastern USA salt marshes. We measured disturbance responses (magnitude and recovery trajectory) of 19 variables. Some variables (shoot density, root biomass, snail density, soil pH, soil strength, soil temperature, elevation) declined sharply, while other variables (crab burrow density, soil organic matter, soil redox) increased sharply, in response to the burrowed and grazed conditions at the creek head. These variables recovered over subsequent years or decades. Other variables (shoot height, aboveground biomass, rhizome biomass, light interception) declined sharply in the creek head, then overshot control values before recovering. Some variables (benthic algae, soil salinity) did not appear to be disturbed by the creek head. As hypothesized, plants recovered before soils and snails. Disturbance magnitude and time to recovery were often greater directly adjacent to the new creekbank than for the same variables in a parallel transect further away from the creekbank, and in some cases variables never converged with control values, indicating a persistent state change. Reducing the dimensionality of the data set into principal component axes obscured the diverse ways in which different aspects of the system responded to and recovered from the perturbation. Our study illustrates the challenges in moving from simple conceptual models of disturbance to empirical studies in which multiple variables are likely to be affected differently and follow different recovery trajectories.

Kynurenic Acid Protects Against Reactive Glial-associated Reductions in the Complexity of Primary Cortical Neurons - Kate O’Reilly; Katherine O’Farrell; Oivind Midttun; Yuliia Rakovets; Jennifer David -Bercholz; Andrew Harkin (Journal of Neuroimmune Pharmacology, 2021)

Diversity of demersal and megafaunal assemblages inhabiting sandbanks of the Irish Sea - Javier Atalah; Jayne Fitch; Jennifer Coughlan; Julien Chopelet; Ilaria Coscia; Edward Farrell (Marine Biodiversity, 2013)

Platinum anticancer agents and antidepressants: desipramine enhances platinum-based cytotoxicity in human colon cancer cells - Peyman Kabolizadeh; Brigitte J. Engelmann; Nicholas Pullen; Jennifer K. Stewart; John J. Ryan; Nicholas P. Farrell (JBIC Journal of Biological Inorganic Chemistry, 2012)